2021
DOI: 10.1001/jamanetworkopen.2021.39604
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment of Clinical Seizures vs Electrographic Seizures in Full-Term and Near-Term Neonates

Abstract: This randomized control trial determines if the active management of electrographic and clinical seizures in encephalopathic term or near-term neonates improves survival free of severe disability at 2 years of age compared with only treating clinically detected seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…48) How ever, a recent study reported no difference in mortality or longterm morbidity in neonates treated after clinical or electrical events with some concern with worse cognitive function in those with electrographic seizures. 49) Briefly, the threshold for escalation of therapy to decrease seizure burden remains an area of active research.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…48) How ever, a recent study reported no difference in mortality or longterm morbidity in neonates treated after clinical or electrical events with some concern with worse cognitive function in those with electrographic seizures. 49) Briefly, the threshold for escalation of therapy to decrease seizure burden remains an area of active research.…”
Section: Treatmentmentioning
confidence: 99%
“…The treatment of electrographic seizures is ideally time-critical, as infants treated within 1 hour of seizure onset had the lowest seizure burden and fewer seizures over the subsequent 24 hours [ 48 ]. However, a recent study reported no difference in mortality or long-term morbidity in neonates treated after clinical or electrical events with some concern with worse cognitive function in those with electrographic seizures [ 49 ]. Briefly, the threshold for escalation of therapy to decrease seizure burden remains an area of active research.…”
Section: Treatmentmentioning
confidence: 99%
“… A key goal of neonatal neurocritical care is improved outcomes, and brain monitoring plays an essential role. The recent NEST trial 1 reported no outcome benefits using aEEG monitoring compared to clinical seizure identification among neonates treated for seizures. However, the study failed to prove the effects of monitoring on seizure treatment in the first place.…”
mentioning
confidence: 99%
“…The aim of this trial was to evaluate whether aggressive treatment of electrographic seizures in addition to clinical seizures improved neurodevelopmental outcomes compared to treatment of only clinical seizures 1 . Authors took a pragmatic approach to seizure diagnosis by utilizing amplitude‐integrated EEGs (aEEG).…”
mentioning
confidence: 99%
“…Following this publication, the diagnosis and treatment of seizures in neonates has shifted dramatically, and standard of care has since evolved to treatment of all electrographic seizures when possible 9 . Subsequent recruitment for the study by Hunt et al had to end prematurely due to slow enrolment secondary to loss of equipoise of treating clinicians 1 . Thus, the study is ultimately unable to make definitive conclusions on the impact of treatment of electrographic versus clinical seizure treatment on neurodevelopmental outcomes.…”
mentioning
confidence: 99%